Enhancing Maternal Mental Health Knowledge through Hypnocomfort Pregnancy Multimodal Psychoeducation Media - Jannah, Nurul; Winta, Mulya Virgonita I; Pratiwi, Margaretha Maria Shinta (Qualitative and Quantitative Research Center, 2024)
Educational technology plays an important role in increasing access to information, promoting health awareness, and supporting interactive community learning on health issues. The multimodal psychoeducation approach allows the delivery of information through various channels (audio, visual, digital text), which can increase information absorption and emotional engagement. Maternal mental health is a crucial aspect that affects the well-being of both the mother and the fetus during pregnancy. This study aims to evaluate the impact of using multimodal psychoeducational media, specifically hypnocomfort pregnancy, to enhance maternal mental health knowledge in managing anxiety during pregnancy. The research employs a quasi-experimental design with a pre-test and post-test with a control group design. The sample consists of 20 pregnant women. The intervention group receives training using hypnocomfort pregnancy multimodal psychoeducational media. The results indicate that the intervention group experienced a higher maternal mental health knowledge increase than the control group. The T-test results show a significant P-value (0.000), indicating that the use of hypnocomfort pregnancy multimodal psychoeducational media has a significant effect on improving maternal mental health knowledge. It can be concluded that the development and application of hypnocomfort pregnancy multimodal psychoeducational media is effective in enhancing maternal mental health knowledge. This study supports the use of multimodal media in maternal mental health care and recommends integrating similar methods into pregnancy support programs. In addition, broader contributions include the development of psychoeducational methods that can be implemented in health education with the potential to improve the knowledge and management of community mental education.